Herbivory defense in Mimulus quttatus (yellow monkeyflower): consequences for generalist and specialist herbivores - Montenero, Michael (My University, 2012)
Plants have undergone strong selection from herbivory, resulting in diverse physical and chemical defenses. Chemical defenses deter generalist herbivores, but are often tolerated by specialists. Mimulus guttatus (yellow monkeyflower) is a model genetic system with ecological relevance and has physical and chemical defense mechanisms. To examine the effects of these defenses on herbivores, we conducted feeding trials with M. guttatus and larvae of the specialist herbivore Junonia coenie (buckeye caterpillar) and the generalist herbivore Grammia incorrupta (woolly bear caterpillar). Specialist growth rate significantly exceeded generalist growth rate. In addition, number of trichomes, a physical defense of M. guttatus, showed a significant inverse relationship with specialist herbivore growth. In our research, specialists grew the most on M. guttatus, but generalists were most resistant to physical defense.
13 p.
Keywords: Entomology; Biochemistry